SUPLEMEN BAHAN AJAR IPAS MATERI WUJUD ZAT DAN PERUBAHANNYA KELAS IV SEKOLAH DASAR - Ilmansyah, Uray; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to develop and produce additional teaching materials on the topic "Substances and Their Changes" for fourth-grade elementary school students. This research uses a research and development methodology with a mixed approach, following the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. During the product development phase, the researcher conducted product trials with 33 fourth-grade students at state elementary school 17 in Pontianak city. The result of this research is a validated teaching resource designed to enhance learning and increase students' knowledge about the states of matter and their changes. The validity criteria are classified into "very valid", "valid", "less valid", "invalid", and "very invalid". Meanwhile, the validation conducted by design experts resulted in an average score of 4.3, classified as "very valid", while material experts also provided a validation score of 4.3, which is also categorized as "very valid". Furthermore, the large-scale product testing achieved an average score of 4.4, reflecting the criteria of "very good", therefore this product has met the criteria as a good product for learners that can serve as a guide for students to enhance their knowledge, especially on the subject of states of matter and its changes in 4th grade at the elementary school level.